3-Year Efficacy and Durability of Simplification to Single Tablet Regimens: A Comparison between Co-Formulated Efavirenz/Emtricitabine/Tenofovir and Rilpivirine/Emtricitabine/Tenofovir. Issue 2 (February 2018) - Gagliardini, Roberta; Bandera, Alessandra; Zaccarelli, Mauro; Sterrantino, Gaetana; Latini, Alessandra; D'Avino, Alessandro; Lapadula, Giuseppe; Antinori, Andrea; Cauda, Roberto; De Luca, Andrea; Gori, Andrea; Giambenedetto, Simona; et al.
Background: Few data are available about efficacy and durability of simplification from multi-tablet antiretroviral regimens to co-formulated efavirenz (EFV)/emtricitabine (FTC)/tenofovir (TDF) versus rilpivirine (RPV)/FTC/TDF in virologically suppressed HIV-1-infected patients. Methods: We retrospectively analysed HIV-infected patients with HIV RNA <50 copies/ml switching to co-formulated EFV/FTC/TDF or RPV/FTC/TDF at five Italian centres. Patients were followed from time of switch until regimen discontinuation or a maximum of 3-years follow-up. Time to treatment discontinuation (TD) and virological failure (VF; defined as two consecutive HIV RNA >50 copies/ml or a single determination >1, 000 copies/ml) and their predictors were investigated. Results: 1, 560 patients were reviewed of which 1, 097 (70%) switched to EFV/FTC/TDF and 463 (30%) to RPV/FTC/TDF. During follow-up, VF and TD occurred in 44 (4%) and 242 (22%) patients in EFV/FTC/TDF and in 29 (6%) and 50 (11%) patients in RPV/FTC/TDF, respectively. The 3-year estimated probability of remaining free from VF was 96.2% with EFV/FTC/TDF versus 92.7% with RPV/FTC/TDF ( P =0.003). At multivariate analysis, regimen type (EFV/FTC/TDF versus RPV/FTC/TDF aHR 0.24; P =0.004) and time of virological suppression (aHR 0.85; P =0.048) were the only independent predictors of VF. The estimated 3-year probability of remaining free from TD was 77.4% with EFV/FTC/TDF versus 88.4% with RPV/FTC/TDF ( P =0.001). Predictors of TD were female sex, switching from PI-based regimens, older age, shorter time of virological suppression and regimen type (EFV/FTC/TDF versus RPV/FTC/TDF aHR 2.48; P <0.001). RPV/FTC/TDF showed a safer lipid profile and a greater increase in creatinine. Conclusions: Both regimens showed good safety and efficacy in this real-life setting, although switch to RPV/ FTC/TDF seemed better tolerated while EFV/FTC/TDF was associated with a lower probability of VF.